Efficacy and safety of follitropin delta versus follitropin alpha/beta in infertility treatment: A systematic review and meta‐analysis - Shinnosuke Komiya; Jun Watanabe; Takero Terayama; Kyosuke Kamijo; Hidetaka Okada (Reproductive Medicine and Biology)
Abstract Background Follitropin δ may be an alternative to conventional follitropin α/β for controlled ovarian stimulation (COS) within assisted reproductive treatment (ART), but its efficacy and safety remain unknown. We performed a random‐effects meta‐analysis to compare the efficacy and safety of follitropin δ and follitropin α/β. Methods We searched randomized controlled trials comparing follitropin δ and follitropin α/β using MEDLINE, Embase, CENTRAL, ClinicalTrials.gov, and WHO‐ITCRP on December 14, 2022. The primary outcomes were the live birth rate and the incidence of moderate or severe ovarian hyperstimulation syndrome (OHSS). The certainty of the evidence was assessed using the grading of recommendations assessment, development, and evaluation approach. The protocol was registered on the Open Science Framework. Results Three studies involving 2682 participants were included in our meta‐analysis. The results indicated that follitropin δ may result in little to no difference in live birth rates (risk ratio [RR], 1.12; 95% confidence interval [CI], 0.91–1.38; low certainty) and the incidence of moderate or severe OHSS (RR, 0.78; 95% CI, 0.48–1.26; low certainty) compared with follitropin α/β. Conclusion Follitropin δ may result in little to no difference in COS compared with follitropin α/β, especially in terms of live births and safety.